(untitled) (Journal of actual problems of jurisprudence, 2024)
The active globalization processes observed in the sphere of economic and political activity have negatively affected the qualitative and quantitative indicators of mercenary crime in the real estate sector. The complication of forms of criminal activity due to the combination of criminal and legal mechanisms of real estate turnover actually leveled the role of previous preventive measures and caused the need to develop new mechanisms of legal influence on mercenary crime adapted to modern criminal challenges, which would be based on a deep systematic analysis of modern fraud in the real estate sector. The construction business in the Republic of Kazakhstan has a large turnover of investment and budget funds and is an extremely attractive area for criminals. Various types of transactions are concluded in the real estate market, and the turnover of funds in the construction sector alone amounts to billions of US dollars. The analysis of scientific research of modern Kazakh science shows the absence of such, whereas a comprehensive study of the legal and criminological nature of fraud in real estate, taking into account the peculiarities of criminalization of the act in question, is necessary. The article analyzes the specifics of real estate as an object of fraud, examines the main types of such fraud and analyzes the measures that are carried out and should be carried out in order to avoid such illegal actions. Keywords: crime, real estate, fraud, real estate fraud, criminology.